Increasingly enhanced water resources management effectively promotes the synergistic development of ecosystem services in inland river basins in arid regions – a case study of Tarim River - Ayong Jiao; Xiaoya Deng; Yanming Gong; Hongbo Ling (Ecological Indicators, 2025)
Arid inland river basins face severe water scarcity and uneven seasonal distribution, crucial for maintaining ecosystem services (ESs). Water availability and management directly impact ecosystem health and stability. This study focuses on the Tarim River Basin to assess how ecological water conveyance projects and watershed reforms affect ESs and to identify mechanisms behind ESs’ responses to natural and human factors. Using InVEST, RWEQ, CASA, and OPGD models, we analyzed the spatiotemporal changes and drivers of ESs under strengthened water management. From 2000 to 2010, net primary productivity (NPP) and carbon storage (CS) slightly rose by 0.2% and 2.0%, while habitat quality (HQ) and windbreak and sand fixation (WS) dropped by 8.9% and 57.6%. Synergies between NPP-HQ and CS-NPP improved, but others weakened. From 2010 to 2020, after intensified management, NPP, CS, HQ, and WS increased by 18.8%, 0.1%, 0.1%, and 66.7%, with stronger synergies. Enhanced management improved groundwater and vegetation cover. The interaction of groundwater depth and NDVI was key to boosting CS, HQ, and NPP. The findings of this study not only provide important guidance for enhancing ESs in the Tarim River region but also offer new perspectives and scientific foundations for ecological protection and efficient resource management in other arid inland river basins worldwide, supporting sustainable development in these areas.